Impact of Eucheuma cottonii Extract on Rattus norvegicus Renal Function Test Caused by Monosodium Glutamate - Fitri Handajani; Nabil Nabil; Hanggara Rahmabrata (Biomedical and Biotechnology Research Journal)
Background: Eucheuma cottonii (EC) is a seaweed contains active compounds of alkaloids, flavonoids, saponins, and triterpenoids as antioxidants. Monosodium glutamate (MSG) is a chemical widely consumed as a flavor enhancer. The use of MSG in large amounts and for long durations triggers organ damage, including the kidneys, which is currently still a debate. This study aims to prove whether EC extract can reduce kidney damage due to MSG induction. Methods: This was an experimental animal study with probability sampling. Twenty-four Rattus norvegicus were divided into three groups: Group I without treatment, MSG-induced, Group II at 4 g/kg BW intragastric on the 7th day for 14 days, and Group III was induced by MSG and given EC extract at 400 mg/kg body weight (BW) intragastric on the 10th day via intragastric tube for 14 days. At the end of the study, blood samples of experimental animals were taken to examine blood urea nitrogen (BUN) and serum creatinine. Kolmogorov–Smirnov test and Levene’s test for homogeneity. Results: MSG induction increased BUN levels but did not increase serum creatinine levels. The group induced by MSG and given EC extract compared to the group induced only by MSG showed no significant difference in all variables. Conclusion: MSG induction at 4 g/kg intragastrically for 14 days increased BUN levels but did not increase serum creatinine levels. EC extracts at 400 mg/kg BW in R. norvegicus-induced MSG at 4 g/kg intragastrically for 14 days did not significantly reduce BUN and serum creatinine levels.